Yazoo, or, On the picket line of freedom in the South : a personal narrative - Morgan, A. T. (Albert Talmon) (Southern classics series., 2000)
"Yazoo is a firsthand account of Reconstruction told by a Wisconsin carpetbagger and devout abolitionist who moved to Mississippi in pursuit of wealth and social reform. Seeking economic opportunity for himself as well as a chance to bring about a new social order in the defeated South, Albert T. Morgan leased a cotton plantation in Yazoo County, Mississippi, in 1865. His farming venture failed - as did his efforts to secure interracial democracy - but his decade spent in Yazoo County brought him opportunities to serve in elected office as a constitutional delegate, state senator, and county sheriff and supervisor. The decade also gave him an intimate understanding of the trials and tribulations associated with the freedmen's struggle for equality.